Posterior unilateral approach with 270° spinal canal decompression and three-column reconstruction using double titanium mesh cage for thoracic and lumbar burst fractures - Shi, Lei; Ge, Qi-jun; Cheng, Yun; Lin, Lu; Yu, Qing-Shuai; Cheng, Si; Chen, Xiao-Lin; Shen, Hong-Quan; Chen, Fu; Yan, Zheng-jian; Wang, Yang; Chu, Lei; et al. (Frontiers in Surgery, 2023)
Objective：To evaluate the clinical effects of the posterior unilateral approach with 270° spinal canal decompression and three-column reconstruction using double titanium mesh cage (TMC) for thoracic and lumbar burst fractures. Materials and methods：From May 2013 to May 2018, 27 patients with single-level thoracic and lumbar burst fractures were enrolled. Every patient was followed for at least 18 months. Demographic data, neurologic status, back pain, canal compromise, anterior body compression, operative time, estimated blood loss and surgical-related complications were evaluated. Radiographs were reviewed to assess deformity correction, anterior body height correction, bony fusion and TMC subsidence. Results：The average preoperative percentages of canal compromise and anterior body height compression were 58.4% and 50.5%, respectively. All surgeries were successfully completed in one phase, the operative time was 151.5±25.5 min (range: 115~220 min), the estimated blood loss was 590.7±169.9 ml (range: 400~1000 ml). Neurological function recovery was significantly improved except for 3 grade A patients. The preoperative visual analog scale (VAS) scores for back pain were significantly decreased compared with the values at the last follow-up (P=0.000). The correct deformity angle was 12.4±4.7° (range: 3.9~23.3°), and the anterior body height recovery was 96.7%. The TMC subsidence at the last follow-up was 1.3±0.7 mm (range: 0.3~3.1 mm). Bony fusion was achieved in all patients. Conclusion：The posterior unilateral approach with 270° spinal canal decompression and three-column reconstruction using double TMC is a clinically feasible, safe and alternative treatment for thoracic and lumbar burst fractures.